Motivasi Menikah Lagi : Studi Kasus Pasangan Suami Istri dari Seorang Janda dan Duda yang Menikah Lagi di Usia Lanjut - Syah, Lutfi Anshori; Mulyadi, Mulyadi (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2016)
Remarriage is starting a new marriage relationship between widow or widower with someone. Remarriage of the elderly is commonly happening nowadays. Remarriage is one of the ways done by the elderly to solve problem of loneliness and sexual intercourse loss due to the unavailability of the couples. The focus of this study are, how the motivation of widow and widower couples getting remarried in the elderly age, how the pattern of adaptation of the couples after marriage, and the implication of remarrying in the old age to the family. This research is designed as qualitative research by doing interview, observation, and documentation. The subject taken for this research is a couple of a widow and widower who remarry. The results of data analysis show that motivation possessed by a widow and a widower who remarry in their old age is that they want to elide loneliness and leisure, need of a couple, need composure in worship and need of happiness. The level of happiness within elderly couple who remarries is depend on adaptation process before and after marriage, adapting to each other and to the couple’s children, and support from each of both families.